PATTERNS, DETERMINANTS AND CONSEQUENCES OF MIGRATION AMONG IGBO WOMEN IN LAGOS, NIGERIA (2014)
Studies have shown that the Igbo are one of the most migratory ethnic groups in Nigeria with more than half of the internal migrants being women. Most Igbo internal migrants go to the western part of the country of which Lagos is the most preferred destination. Although studies exist on internal migration in Nigeria, negligible attention has been paid to female migration and the associated motivating factors. This study, therefore, examined the determining factors as well as the consequences of migration among Igbo women in Lagos, Nigeria. Giddens’ Structuration theory and Harris-Todaro theory of migration were used as the theoretical framework. A descriptive design was employed. Multistage sampling was used to select 630 respondents. This involved selection of 2 Local Government Areas (LGA) from each senatorial district and 10 Enumeration Areas from each LGA; and household screening to identify and select respondents. A structured questionnaire was used to collect data on background characteristics of respondents, patterns, motivations for migration, and consequences of migration. Twenty-five In-depth Interviews (IDIs) were conducted among Igbo female migrants. Six Focus Group Discussions (FGDs) were conducted on the basis of specific identities such as rural and urban origins, never married, married, migrated alone, and migrated in company of husband or relative. Descriptive statistics, Chi-square and logistic regressions were used to analyse quantitative data at 0.05 level of significance while qualitative data were analysed using the thematic approach. The median age of the migrants was 35 years. More than half (58.6%) migrated from rural areas; 41% migrated in stages from rural to rural or urban areas before moving to Lagos; 86% of those who migrated from the urban area migrated in stages. The major determinant of migration was economic. Those who migrated to improve business activities were 56.2%. Only 7.3% migrated to join their husband and/or family. Over half (53.2%) migrated independently. Migration had positive effects on some migrants as 48.9% were unemployed before migration while only 17.8% were unemployed a year after migration. The likelihood of migrating independently significantly increased by employment status and educational qualification OR= 0.27; and OR= 3.61. There was a significant change in marital status before and after migration (χ2 =107.96). Above two-thirds (67.3%) realised their goals for migration. Duration of stay and change in income significantly predicted the likelihood of realization of goals (OR= 2.75; and OR= 9.62). The FGD revealed that non-economic factors such as hope of getting married and to seek solace from a broken relationship also motivated migration; while IDI showed that most migrants experienced considerable social mobility and empowerment. Many Igbo female migrants to Lagos are independently migrants and were motivated mainly by economic factors. Therefore, government should create enabling social-economic environment in Lagos to enable migrants realise their economic aspirations.